Internal and External Workload in National and International Netball Competition - Eijwoudt, S; Andrews, T; McErlain-Naylor, SA; Stewart, T; Spencer, K (Informa UK Limited, 2023)
Differences in workload exist between netball playing positions and competition levels, but no research has compared workloads experienced by the same elite players during national and international competitions. This study collected internal (heart rate) and external (PlayerLoad·min−1) workload data per match quarter from 44 players during a national competition and 12 players during an international competition. Nine players played in both competitions. Linear mixed models compared percentage of match quarter in each heart rate zone and PlayerLoad·min−1 between competitions for each playing position. Workloads against low- and high-ranked international opponents were also compared. Internal workloads were greater in national compared to international competition for GD and WD positions. PlayerLoad·min−1 was significantly higher by 8–13% in the national competition for positions WD and C, and by 5–8% in the international competition for GD and GA. Positional differences may indicate a role of the team’s tactical style of play. Workloads were generally greater against higher- rather than lower-ranked international opponents. These results indicate that tactical factors in combination with playing position and opposition characteristics should be considered when preparing physically for matches.
Keywords: Netball; heart rate; international; training load; workload; 32 Biomedical and Clinical Sciences; 5201 Applied and Developmental Psychology; 42 Health Sciences; 3202 Clinical Sciences; 4207 Sports Science and Exercise; 52 Psychology; 1106 Human Movement and Sports Sciences; 1302 Curriculum and Pedagogy; Sport Sciences; 3202 Clinical sciences; 4207 Sports science and exercise; 5201 Applied and developmental psychology; Humans; Basketball; Workload; Athletic Performance; Heart Rate; Linear Models; Humans; Linear Models; Heart Rate; Basketball; Workload; Athletic Performance; Humans; Basketball; Workload; Athletic Performance; Heart Rate; Linear Models